PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 005 BATU GAJAH - Ernawati, Ernawati; Alpusari, Mahmud; Daud, Damanhuri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstraction: This research is conduted by the low students? achievement in social lesson, with the average class score is 67,8. Whereas minimum criteria passing grade the social completeness 57,14%. The formulations of the problem: ?is the implementation of corporative model of learning type TPS can increase students? Achievement in social for four grades students of public elementary school 005 Batu Gajah Pasir Penyu Sub district Indragiri Hulu Regency ??. The Research Goal is to increase the study achievement in Social lesson by four grade students of Public Elementary School 005 Batu Gajah with the implementation of corporative Model Type Think Pair Share (TPS). This research was conducted in 3th March until 10th March 2015 with two phases. The Subject of this research is the students of Public Elementary School 005 Batu Gajah four grades with 28 students become a data sources. This research is the Classroom Action Research (PTK). Classroom Action Research is a research that is conduted due to the problem a rise in the class. The Instrument Collecting Data in this thesis is Syllabus, Lesson Plan (RPP) and students Worksheet (LKS). This thesis showed the students achievement which is gained from the daily examination before action with average score is 72,35 and increase in first phase with average 78,64 and second phase becomes 91,66%. The result of data analysis students activity in phase first meeting is 58,33% an at the school phase increased to 75%. Second Phase in the first meeting 79,16% and second meting increased become 91,66%. The result of this research in class IV Cooperative Learning Model Type TPS can increase the students? achievement and can be one of the alternative choices to increase teaching and learning process.Key word : Cooperative Learning Model Type TPS. Outcome IPS